Peran perempuan dalam pemerintahan desa: studi kasus di desa langkap kecamatan burneh kabupaten bangkalan - Mahsusiyah, St. Mahsusiyah (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
The main problem in this research is the role of women in the village government, especially in Langkap village. This is due to an increase in women's participation in the village government, which primarily the structure of the village government consists of men, but now women are also involved in the village government structure, where six women participate in the village government in Langkap village. The method used in this research is descriptive qualitative with the data collection techniques by observation, interviews, documentation studies, and from several books, scientific works related to this research. The results and findings of this research indicate that the role of women in the village government they involve and participate in planning, drafting, and implementing discretion in the village government. The impact of the women in the realm of government, such as in terms of community policies, health, and village businesses. Meanwhile, the obstacle for women in carrying out their roles is approval from their family or husband. The women who are involved in the village government structure hope that in the future can be more active in carrying out the roles in the village government. The women who are not participating at the moment can learn together to increase their knowledge and build the enthusiasm to begin actively participating in the village government.